ANALISIS PEMBUATAN COWL DRAPERY DENGAN TEKNIK DRAPING PADA BUSANA - Nurlita, Ela; Yasnidawati, Yasnidawati (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Abstract. This study aims to describe the results of cowl drapery using the draping technique. The type of research used is applied research. The object of research is cowl drapery using draping technique. The research instrument uses an assessment format with a Likert Scale. The assessment is carried out by 3 panelists, namely lecturers who are experts in the field of clothing, by fitting. The data analysis technique used is quantitative descriptive and inferential analysis. The results of the cowl drapery using the draping technique show that the results of the cowl drapery using the draping technique obtained an assessment result with a percentage value of 80.21% categorized as appropriate. Based on the t-test, it was found that the average results were significant between the results of cowl drapery using the draping technique with a significance level of 0.05. Keywords: Cowl drapery; draping; Abstrak. Penelitian ini bertujuan untuk untuk mendeskripsikan hasil cowl drapery menggunakan Teknik Draping. Jenis penelitian yang digunakan adalah penelitian terapan. Objek penelitian yaitu cowl drapery menggunakan teknik draping. Instrumen penelitian memakai format penilaian dengan Skala Likert. Penilaian dilakukan oleh 3 orang panelis yaitu dosen yang ahli dalam bidang busana, dengan cara fitting. Teknik analisis data yang digunakan adalah deskriptif kuatitatif dan analisis inferensial. Hasil cowl drapery menggunakan Teknik Draping menunjukkan hasil cowl drapery menggunakan teknik draping didapatkan hasil penilaian dengan nilai persentase sebesar 80.21 % dikategorikan Sesuai. Berdasarkan uji t didapatkan hasil rata-rata penilaian yang signifikan antara hasil jadi cowl drapery menggunakan teknik draping dengan taraf signifikansi sebesar 0.05. Kata Kunci: Cowl drapery; draping;